Complete auricular avulsion and reconstruction techniques: a literature review - Manar A. Awad; Mahmoud A. Deshisha; Yasmin Z. Salam; Hadir M. Abou Mostafa; Mohamed G. Ibrahim; Ihab M. Nada (The Egyptian Journal of Otolaryngology)
Abstract Background Auricular avulsion can cause severe psychological effects. There are no established protocols for surgical treatment for such injuries. Acute care involves various procedures like graft reattachment, skin flap reconstruction, Baudet approach, and microvascular repair. Objectives Reviewing the literature regarding various reattachment techniques for managing complete auricular avulsion was the goal of this review. It also aimed to help the surgeon choose the best total reconstruction method considering the available materials and to assess the advantages and disadvantages of each technique. Methods We thoroughly reviewed relevant research on publications describing total auricular avulsion repaired with reattachment which were indexed in PubMed, MEDLINE, and Scopus. The study accepted and reviewed English-language papers without determining their publication date, using a database search based on key words. Conclusions According to the literature, microvascular restoration is more successful for avulsed ears, although composite grafts are better aesthetically. Early hyperbaric oxygen and surgical treatment can improve patient outcomes. Recently, 3D printing is a big step forward in auricular reconstruction, providing a patient-specific, customizable, and efficient alternative for people with auricular loss.